Effectiveness of Social Studies Learning Through Tik Tok Media to Improve Students' Understanding - Daniati, Nia; Mulyana , Eldi; Rero, Dentiana (SAHUR Journal, 2023)
The development of government policies that require taking steps to close educational facilities from the highest level to the lowest level and require the world of education to implement distance learning with the aim of breaking the chain of transmission of Corona Virus Deseas-19 (Covid-19) The purpose of this study was to find out how far the learning interest of students could increase in understanding the material in social studies learning after the application of learning media through Tik Tok videos to students. The research method used is a quantitative method with an experimental design. The data collection technique used was the pretest and posttest, and the data analysis process to identify increases was carried out by the normalized N-Gain test. The results of this study indicate that there is a significant increase in students' understanding of social studies learning by using tick-tock-based learning media in social studies learning.